Common Battery Anode Testing Protocols Are Not Suitable for New Combined Alloying and Conversion Materials. Issue 23 (24th September 2018) - Bree, Gerard; Geaney, Hugh; Ryan, Kevin M.
Abstract: Here we report an interesting observation on anode materials for lithium ion batteries that undergo combined conversion and alloying lithiation processes during cycling (CAMs). These materials are generating interest as low cost and high capacity alternatives to graphite. We find that common testing protocols (CTPs) are unsuitable for assessment of CAMs due to their distinct multi‐step lithiation characteristics. CTPs involve reporting total gravimetric capacity in a half‐cell configuration alone (opposite Li foil), without individual analysis of each process; energy density and the problems associated with wide discharge voltages are not addressed. Through isolating the individual lithiation processes of a model system (Cu2 ZnSnS4 ), we determine that the conversion processes are highly unstable, whereas the alloying processes exhibit remarkable capacity retention. We demonstrate that inclusion of the conversion processes in cycling actually reduced full cell energy density when compared with alloying alone. This indicates that CTPs may well underestimate the stability of CAMs. It is apparent that the true advantage of CAMs lies in the synergistic combination of the capacity of the alloying portion, and the stability provided by the uncycling Li2 S buffer material. Finally, we prescribe a set of testing protocols for a meaningful assessment of new CAMs. Abstract : For real ! When used to examine combined conversion and alloying anodes, common battery testing protocols often lead to misleading or irrelevant conclusions. In this work, new protocols focusing on meaningful material assessment are developed, which will enable more rigorous screening of proposed anodes, and direct researchers towards materials optimized for real‐world application.